(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article analyzes the schooling process and the educational status of adolescents and young people serving socio-educational measures in closed facilities in the city of Natal, capital of the state of Rio Grande do Norte, Brasil. A critical-reflective analysis was adopted, based on the historical-dialectical materialist perspective, using a literature review, document analysis, and unsystematic observation of data and information, with a qualitative and descriptive emphasis. The results indicate that the low level of education among this population is driven by a deficient schooling process, primarily caused by school dropout. Furthermore, it was found that this educational deficit predates the enforcement of socio-educational measures; however, some progress in schooling is observed during this period. The study concludes that it is necessary to develop educational policies and pedagogical approaches that take into account the specific characteristics of the socio-educational system and the institutionalized individuals within it, to effectively address the issue of low educational attainment in this group and to expand their access to other public policies.